2007
DOI: 10.1038/ismej.2007.79
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia oxidation and ammonia-oxidizing bacteria and archaea from estuaries with differing histories of hypoxia

Abstract: Nitrification, the oxidation of NH 4 þ to NO 2 À and subsequently to NO 3 À , plays a central role in the nitrogen cycle and is often a critical first step in nitrogen removal from estuarine and coastal environments. The first and rate-limiting step in nitrification is catalyzed by the enzyme ammonia monooxygenase (AmoA). We evaluate the relationships between the abundance of ammoniaoxidizing archaea (AOA) and ammonia-oxidizing bacteria (AOB) amoA genes; potential nitrification rates and environmental variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
210
6
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(248 citation statements)
references
References 19 publications
29
210
6
3
Order By: Relevance
“…b-AOB genes, in contrast, were only detected in 59% of samples and in much lower abundance. This result is consistent with an earlier study of subtropical estuarine sediment, which showed that AOA are ubiquitous in sediments, whereas b-AOB were found in only 40% of samples (Beman and Francis, 2006) and suggests that AOA and not AOB may be responsible for the majority of nitrification in estuarine sediments (Caffrey et al, 2007;Lam et al, 2007). The lack of consistent correlation in the abundance of AOA and b-AOB, suggests that there are different factors driving their proliferation in the Fitzroy river.…”
Section: Discussionsupporting
confidence: 81%
“…b-AOB genes, in contrast, were only detected in 59% of samples and in much lower abundance. This result is consistent with an earlier study of subtropical estuarine sediment, which showed that AOA are ubiquitous in sediments, whereas b-AOB were found in only 40% of samples (Beman and Francis, 2006) and suggests that AOA and not AOB may be responsible for the majority of nitrification in estuarine sediments (Caffrey et al, 2007;Lam et al, 2007). The lack of consistent correlation in the abundance of AOA and b-AOB, suggests that there are different factors driving their proliferation in the Fitzroy river.…”
Section: Discussionsupporting
confidence: 81%
“…Decreasing soil temperature was correlated with increasing AOA abundance, which is in contrast to the results of a soil microcosm study by Tourna et al (2008). However, Urakawa et al (2008) and Caffrey et al (2007) investigated marine ecosystems in which decreased phylogenetic diversity and abundance of AOA were found with increasing temperature, respectively. Based on these contradictory results, we suggest further experiments under field conditions to substantiate that decreasing soil temperature promotes AOA abundance.…”
Section: Discussioncontrasting
confidence: 54%
“…These studies often revealed the dominance of archaeal over bacterial ammonia oxidizers (Francis et al, 2005;Wuchter et al, 2006;Mincer et al, 2007;Agogué et al, 2008;Newell et al, 2013). Further support for the strong role for AOA in nitrification comes from observations of the co-occurrence of archaeal amoA in areas of nitrification activity (Caffrey et al, 2007;Beman et al, 2008;Alves et al, 2013) and from metatranscriptomic studies (Baker et al, 2012;Lesniewski et al, 2012). However, to determine the actual contribution and impact of AOA on the nitrogen cycle requires measurements of ammonium oxidation rates, as they cannot be deduced from transcript abundance alone (Mu mann et al, 2011), given that quantification is influenced by, for example, mRNA degradation during sampling (Feike et al, 2012) and, in addition, may not inevitably reflect environmental activity.…”
Section: Introductionmentioning
confidence: 97%